A Neuropsychological Profile for Cerebrotendinous Xanthomatosis: A Single-Case Study. (3rd April 2020) - Bryant, Andrew M.; Block, Cady
Abstract: Objective: Cerebrotendinous xanthomatosis (CTX) belongs to a heterogeneous group of neurological disorders known as autosomal recessive cerebellar ataxias. Low awareness of CTX can result in misdiagnoses in the differential diagnostic process and may limit one's ability to offer suitable recommendations. While neurodegeneration is a recognized manifestation of CTX, there is scant literature to characterize the nature of cortical symptoms and even less detailing of its associated neurocognitive and neuropsychiatric manifestations. Method: Based on the lack of representation of CTX in neuropsychological literature, we sought to present a case seen in a 39-year-old patient within our own clinic. Results: Evaluation of the patient's neurocognitive functioning revealed global impairment consistent with a CTX diagnosis and neuroimaging findings noting significant cerebellar involvement. Conclusions: Neuropsychologists are increasingly called upon to make treatment recommendations and provide information that may be helpful in differential diagnosis as part of multidisciplinary teams. Referrals from neurology are common, and it is important for neuropsychologists to be aware of diseases that affect the central nervous system; CTX is one such example. The goal of this case study is to build awareness of this condition and increase interest in a more systematic approach to research and clinical care of this population.